Kalimatun Sawa in the Perspective of Indonesian's Interpretation - Qurrata A'yun; Hasani Ahmad Said (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2019)
This study examines the interpretation of the ulama of Indonesia regarding kalimatun saw‘ which as recited in QS. li ‘Imrn verse 64. The method of this study is qualitative research that produces descriptive data in the form of conclusions delivered verbally by thematic methods. The author explains the meaning of kalimatun saw‘ and its interpretation according to the ulama of Indonesia which in this case focused on four ulama. They are Syaikh Nawawi al Bantani in Tafsir Marh Labd, Hasbi ash-Shiddieqy in Tafsir Al-Qur’anul Majid an-Nuur, Buya Hamka in Tafsir Al-Azhar, and M. Quraish Shihab in Tafsir al-Misbh. The analysis was done in order to infer the meaning of kalimatun saw‘ in general. The conclusion of this study is the meaning of kalimatun saw‘ is the same, fair, balanced and there is no dispute in it. The phrase forbids humans to worship other than Allah, not to associate partners with anything, and not making other humans as God.